A Classification of Multi-Axis Features based on Manufacturing Process - Kang, Mujin; Kim, Gyungha; Eum, Kwangho; Park, Myon Woong; Kim, Jae Kwan (KOREAN SOC PRECISION ENG, 2014)
A machining feature can be regarded as the shape of the removal volume through a cutting process, which represents some manufacturing attributes of a part. Since the machining feature can play a crucial role in process planning, it is desirable to name machining features in such a way that a clear correlation between machining features and machining methods are reflected in the feature classification. However; most researches dealing with this topic do not clearly show the relationship between machining features and machining processes. On the other hand, no consensus on the feature classification method exists yet, which causes confusion when using the term "frature". As a result, use of the features has not been very helpful in manufacturing preparation such as machining process selection. In this paper, classification methods of multi-axis machining features known in relevant literatures are studied firstly Secondly, machining characteristics of various features are investigated to find out the relationship between machining features and machining methods. Thirdly, based on the machining methods of features, a logical classification scheme of multi-axis machining features is proposed. And finally, the proposed feature taxonomy is verified through applying to an example part with multi-axis machining features.
Keywords: MACHINING FEATURES; RECOGNITION; COMPONENTS